Os objetos de castigo no museu do homem do Nordeste: objetos de castigo e punição e seus usos nas disputas das narrativas das memórias negras. - Pereira, Anna Karla da Silva (2021)
This work aims to create a catalog based on the collection of instruments of punishment and punishment displayed at the Museu do Homem do Nordeste and documents from the collection; the collection consists of sixteen objects, all exposed to visitors, documents collected between 2018 and 2020. We reflect and highlight the importance they have as a memory and historical, cultural, ethnic and social heritage. The theoretical framework is anchored in the concepts of museology by Possamai (2001), in the memory of Nora (1993) and Halbwachs (2003), representation and identity of Stuart Hall. (2003). The methodology used is supported by the qualitative approach, with the character of exploratory and descriptive research. Museums are condensers of diverse memories and (re) signify the set of their specific objects, their collections; in other words, they keep, conserve, manage and continually print new symbols, meanings and signifiers to their collections. They are institutions for the preservation of memory, using their collection, their heritage to produce a narrative, telling the story of their represented. The documentary research procedures were carried out from technical visits, research in physical and virtual collections. However, we produce these reflections because the physical museum space does not in itself produce narratives, men build museums and place within it the discourse they want to be assimilated and appropriated by its users. What differentiates one museum from another is to whom the speech is addressed. Thus, the design of a museum, as well as its maintenance, is a political strategy. The catalog is also the result of the collection's historiographic survey and seeks to promote a critical debate on the use of exhibitions for the construction of collective memories and power relations.